The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1806-9282.20210640
|View full text |Cite
|
Sign up to set email alerts
|

Can serum 8-hydroxy-2'-deoxyguanosine levels reflect the severity of pulmonary arterial hypertension?

Abstract: OBJECTIVE:Oxidative stress plays a pivotal role in the pathogenesis of pulmonary arterial hypertension. 8-Hydroxy-2'-deoxyguanosine is a sensitive biomarker that reflects the degree of oxidative damage to DNA. We investigated whether serum 8-Hydroxy-2'-deoxyguanosine is a clinically useful biomarker for the severity of pulmonary arterial hypertension. METHODS:We measured serum 8-Hydroxy-2'-deoxyguanosine levels in 25 patients (age 37±13 years, 68% women) diagnosed with idiopathic pulmonary arterial hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…The main finding of this study was that the blood levels of superoxide anion radical did not significantly differ between adults with CHD and their age- and gender-matched healthy controls. This finding is contrary to some other studies that claim the presence of oxidative stress in the peripheral blood of patients with CHD [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], but it is in accordance with three studies showing that there was no significant difference in oxidative stress in the peripheral blood of patients with CHD and healthy individuals [ 46 , 47 , 48 ].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The main finding of this study was that the blood levels of superoxide anion radical did not significantly differ between adults with CHD and their age- and gender-matched healthy controls. This finding is contrary to some other studies that claim the presence of oxidative stress in the peripheral blood of patients with CHD [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], but it is in accordance with three studies showing that there was no significant difference in oxidative stress in the peripheral blood of patients with CHD and healthy individuals [ 46 , 47 , 48 ].…”
Section: Discussioncontrasting
confidence: 59%
“…In our study, only five adult patients with VSD were included; this subgroup was too small to perform a separate statistical analysis. In contrast, in most other studies on oxidative stress in the blood of patients with CHD, indirect nonspecific markers of oxidative stress [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] were used, e.g., the assessment of the activity of oxidative and antioxidant enzymes (superoxide dismutase (SOD), catalase and glutathione peroxidase), levels of antioxidants (vitamin E, uric acid and selenium), levels of malondialdehyde (MDA) and protein carbonyl (PCO), plasma total oxidant status (TOS), total antioxidant capacity or status (TAC or TAS) and oxidative stress index (OSI) as well as the quantification of DNA damage assessed by alkaline comet assay in circulating lymphocytes and levels of 8-hydroxy-2′-deoxyguanosine.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…By the 3rd-5th day of life, in children of group II, we noted an increase in the level of 8-OHdG -4.10±0.42 ng/ml while in group I the quantity of 8-OHdG index decreased -1.06±0.28 ng/ml, p<0.05 (Table 2). Thus, in the group of children with perinatal asphyxia, the level of the OS indicator increases, which also correlates with the average pressure in the pulmonary artery and the severity of PPH [10].…”
Section: Resultsmentioning
confidence: 88%
“…Perspective is studying the oxidative stress biomarkers in PPH and taking into account their dynamics when choosing a ventilation strategy in prematurely born infants. Our previous studies showed a moderate direct correlation between the biomarker of oxidative stressthe urinary 8-OHdG and mean pressure in the pulmonary artery on the 1 st and 3 rd -5 th days of life in prematurely born infants with asphyxia and with asphyxia in combination with RDS, which indicates the presence of a direct relationship between the severity of PPH and the severity of OS [10].…”
Section: Discussionmentioning
confidence: 86%